Effect of older age on diagnostic and prognostic performance of high-sensitivity troponin T in patients presenting to an emergency department - Normann, Jeanette; Müller-Hennessen, Matthias; Biener, Moritz; Vafaie, Mehrshad; Katus, Hugo; Giannitsis, Evangelos (American heart journal, 2012)
The effect of age on diagnostic and prognostic performance of high-sensitivity cardiac troponin T (hs-cTnT) has not been addressed adequately, so far. High-sensitivity cardiac troponin T was measured serially in patients with acute symptoms presenting to our emergency department. We tested the diagnostic and prognostic performance of baseline and serial hs-cTnT concentrations related to age in all consecutive patients with acute coronary syndrome (ACS) (n = 342) or hs-cTnT increases not due to ACS (n = 442).
Gesehen am 16.04.2018